ANALISIS HUKUM TERHADAP HAK-HAK ATAS TANAH SEBAGAI JAMINAN HUTANG DENGAN DIBEBANI HAK TANGGUNGAN - I Dewa Ayu Widyani; L. Elly AM Pandiangan (to-ra, 2015)
ABSTRACT The right on land as debt insurance be burdened by the right of burden as be mentioned in Article 51 only involve the right of ownership, the right of building usage. Because of the validation of the validation of laws about the right of burden as be arranged in Laws No. 4/1996, the right of usage is the right which is be registered and because its characteristics can be taken oven so that can be burdened by the right of burden. It is also can be done to the building on the land which is obligate to be registered and because its characteristics can be taken over so that can be burdened by the right of burden. Of course it is also to the building on land which different of its ownership whereas the principle of horizontal i of custom law, that become basic of UUPA, can be burdened by the right of burden. Kata Kunci:Hak-hak atas tanah yang dapat dibebani hak tanggungan.